The Opening Conference: A Case Study in Undergraduate Co-design and Inquiry-based Learning - Rakrouki, Zak; Gatenby, Mark; Cantore, Stefan; Rowledge, Thomas; Davidson, Tom (International Journal for Students as Partners, 2017)
The separation between “research” and “teaching” in universities has been under increasing challenge from scholars who want to place inquiry-based learning at the centre of higher education. An important approach to challenging established paradigms and structures is to question, and thereby destabilise, role distinctions, relationships, language, and learning spaces. In this article we present a case study of a conference organized in collaboration between staff and students for first-year undergraduates. Reinventing the academic conference space is our aim in challenging assumptions about undergraduate education. As co-designers of the conference, we reflect on the activities and institutional context leading to the creation of the event, its design and implementation, and its impact on the undergraduate learning community.